Study on the rhythm of thermoregulation of growing pigs housed individually within humid and warm environment - WANG Kai-ying; R. Geers (浙江大学学报. 农业与生命科学版, 2004)
4 growing pigs with same weight and breed used were housed individually at thermoneutral environment. One week later, two of these pigs were reared individually in humid and warm environment and the effects of such environment on the rhythm of core body temperature and heart rate of pigs were studied using DSI telemetry system. Results showed that the rhythm of core body temperature and heart rate of growing pigs under humid and warm environment varied significantly: the peak of core body temperature appeared at 22∶00-23∶00, but not at 16∶00-17∶00. And the rhythm of heart rate of pigs housed in humid and warm environment showed no hourly difference, and higher heart rate was sustained in these pigs.